Inter- and intra-specific diversity of Cuban Pinguicula (Lentibulariaceae) based on morphometric analyses and its relation with geographical distribution - Dominguez, Yoannis; Silva, Saura R. da [UNESP]; Panfet Valdes, Cristina M.; Miranda, Vitor F. O. de [UNESP] (Taylor & Francis Ltd, 2014)
Background: Phenotypic variations have been observed in populations of west Cuban Pinguicula species. Such populations occur in patches under different ecological conditions associated with specialised habitats and separated by geographical and ecological barriers, which can lead to morphological differentiation.Aims: To analyse morphological diversity among species and populations of Cuban Pinguicula; and to test if morphological variability is associated with geographical distribution and distance between populations.Methods: We sampled a total of eight populations of P. albida, P. cubensis and P. filifolia and tested for morphometric differences among them by Principal Component Analysis (PCA) and analysis of variance (ANOVA) based on 31 quantitative traits. We also assessed the geographical isolation with respect to morphological distance.Results: The studied species showed high morphological variability at both species and population level. Reproductive characteristics appeared to be more promissory than vegetative ones in distinguishing geographical groups since they clearly defined populations; nevertheless a strong component of individual variation was observed. According to the distance analysis, such morphological variations were correlated with fragmented populations and isolation and allowed the differentiation of two morphotypes of P. albida and two of P. filifolia.Conclusions: We conclude that high phenotypic variation of the analysed species is related to geographical and ecological isolation which have led to the differentiation of morphotypes within species.
Keywords: carnivorous plants; fragmented populations; restricted distribution; morphotype; morphometry; ecological islands; habitat specificity; isolation